Heterostructured WS2‐MoS2 Ultrathin Nanosheets Integrated on CdS Nanorods to Promote Charge Separation and Migration and Improve Solar‐Driven Photocatalytic Hydrogen Evolution. Issue 7 (2nd March 2017) - Reddy, D. Amaranatha; Park, Hanbit; Ma, Rory; Kumar, D. Praveen; Lim, Manho; Kim, Tae Kyu
Abstract: Solar‐driven photocatalytic hydrogen evolution is important to bring solar‐energy‐to‐fuel energy‐conversion processes to reality. However, there is a lack of highly efficient, stable, and non‐precious photocatalysts, and catalysts not designed completely with expensive noble metals have remained elusive, which hampers their large‐scale industrial application. Herein, for the first time, a highly efficient and stable noble‐metal‐free CdS/WS2 ‐MoS2 nanocomposite was designed through a facile hydrothermal approach. When assessed as a photocatalyst for water splitting, the CdS/WS2 ‐MoS2 nanostructures exhibited remarkable photocatalytic hydrogen‐evolution performance and impressive durability. An excellent hydrogen evolution rate of 209.79 mmol g −1  h −1 was achieved under simulated sunlight irradiation, which is higher than the values for CdS/MoS2 (123.31 mmol g −1  h −1 ) and CdS/WS2 nanostructures (169.82 mmol g −1  h −1 ) and the expensive CdS/Pt benchmark catalyst (34.98 mmol g −1  h −1 ). The apparent quantum yield reached 51.4 % at λ =425 nm in 5 h. Furthermore, the obtained hydrogen evolution rate was better than those of several noble‐metal‐free catalysts reported previously. The observed high rate of hydrogen evolution and remarkable stability may be a result of the ultrafast separation of photogenerated charge carriers and transport between the CdS nanorods and the WS2 ‐MoS2 nanosheets, which thus increases the number of electrons involved in hydrogen production. The proposed designed strategy is believed to potentially open a door to the design of advanced noble‐metal‐free photocatalytic materials for efficient solar‐driven hydrogen production. Abstract : Let the sun in : A new design strategy for a CdS/WS2 ‐MoS2 nanocomposite with potential applications as sunlight‐driven photocatalysts for hydrogen production is demonstrated. The observed high rate of hydrogen evolution and remarkable stability may be a result of the ultrafast separation of photogenerated charge carriers and transport between the CdS nanorods and the WS2 ‐MoS2 nanosheets